Sustainable road construction materials incorporating dam sediment and eucalyptus ash waste: A circular economy framework - Nunthanis Wongvatana; Asarut Noorak; Hatairat Poorahong; Pornkasem Jongpradist; Susit Chaiprakaikeow; Pitthaya Jamsawang (Case Studies in Construction Materials)
This study explores the innovative use of dam sediments stabilized with eucalyptus wood ash (EA) and cement as sustainable materials for road construction, advancing waste utilization in infrastructure development. The novelty lies in the optimization of EA, a biomass waste with pozzolanic properties, as a stabilizer, providing a cost-effective and eco-friendly alternative to traditional methods. Destructive tests demonstrated that the optimal mixture containing 10 % EA and cement achieved an unconfined compressive strength of 7.7 MPa after 28 days, marking a 770 % improvement over untreated sediments. California bearing ratio tests yielded a peak value of 55 %, surpassing subbase material standards. Nondestructive tests using free-free resonance revealed strong correlations between compressive strength and wave velocities, with shear and compressional wave velocities reaching 600 and 990 m/s, respectively. Microstructural analyses showed significant formation of calcium silicate hydrate, with a 30 % increase in content, enhancing interparticle bonding and sediment densification. This study also introduces a novel framework for cost analysis, revealing a 6.6-fold reduction in construction costs due to the local availability of stabilized sediments. Furthermore, leaching tests confirmed the environmental safety of the materials, highlighting their potential as a green and economically viable solution for road construction. These findings underscore the innovative integration of waste materials into high-performance construction applications, advancing the principles of circular economy and sustainability.